Pengaruh Kecerdasan Interpersonal Dan Kemandirian Siswa Terhadap Prestasi Hizbul Wathan Di Sdit Muhammadiyah Al-Kautsar KartasuraTahun Ajaran 2015/2016. - Rohman, M.Abdur, Dra. Sri Hartini, S.H., M.Pd (2016)
Extracurricular is one of after school education to develop skills. Hizbul Wathan is extracurricular education in The purpose of this reseach was to determine include : 1) The effect of interpersonal intelligence to Hizbul Wathan achievement at SDIT Muhammadiyah Al-kautsar Kartasura academic year 2015/2016. 2) The effect of student independence to Hizbul Wathan achievement at SDIT Muhammadiyah Al-kautsar Kartasura academic year 2015/2016. 3) The effect of interpersonal intelligence and student independence to Hizbul Wathan achievement at SDIT Muhammadiyah Al-kautsar Kartasura academic year 2015/2016. 4) The influence interpersonal intelligence and student independence improving to Hizbul Wathan achievement at SDIT Muhammadiyah Al-kautsar Kartasura academic year 2015/2016. This type of research quantitative approach to the method of research Ex-Post Facto. The analysis technique used is multiple linear regression, t test, and test f. Based of analysis of data: 1) the equation regression coefficient obtained Y: 52,814+ 0,115X_1+ 0,151X_2. 2) The t test result interpersonal intelligence t_count>t_table3,011 > 2,048, so interpersonal intelligence a positive effect on Hizbul Wathan achievement. 3) Student independence with positive effect on Hizbul Wathan achievement, it is based on t test result t_count (3,011) >t_table (2,048) finished 3,011 > 2,048, so student independence a positive effect on Hizbul Wathan achievement. The test result f F_(count ) value (11,065) >〖 F〗_(table ) (3,35), finished 11,065> 3,35 or significant value 0,000 < 0,05, mean interpersonal intelligence dan student independence together positive effect on Hizbul Wathan achievement at SDIT Muhammadiyah Al-Kautsar Kartasura academic year 2015/2016. Based on the calculation of the relative contribution and effective contribution shows that the variable interpersonal intelligence give the relative contribution of 44,40% and the effective contribution 19,98% to the Hizbul Wathan achievement, variable student independence relative contributed of 55,59% and contributions effective amounted to 25,01% to Hizbul Wathan achievement. While the coefficient of determination (R^2) was obtained to 0,450, so the interpersonal intelligence and student independence contributed 45% to the Hizbul Wathan acievement at SDIT Muhammadiyah Al-Kautsar Kartasura Academic Year 2015/2016.